Effects of pH and Available Chlorine Concentration of Slightly Acidic Electrolyzed Water on Rice Seed Germination and GABA Accumulation - Tiangang Hou; Fangming Cui; Hongguang Cui; Cuihong Liu; Mingjin Xin; Liyan Wu (Agriculture, 2025)
Previous studies have demonstrated that slightly acidic electrolyzed water (SAEW) treatment can enhance rice seed growth and promote the accumulation of γ-aminobutyric acid (GABA), a bioactive compound. However, the underlying mechanisms remain unexplored. This study systematically investigated the effects of pH and available chlorine concentration (ACC) of SAEW on rice seed germination and GABA biosynthesis. The changing trends were monitored within 7 days. The results revealed that the treatment group with moderate pH (S2, pH 5.74 ± 0.04) showed significantly higher GABA accumulation (71.27 ± 0.45 mg/100 g) compared with S1 (pH 5.04 ± 0.03) and S3 (pH 6.38 ± 0.04) (p < 0.05). Furthermore, a positive correlation was observed between ACC levels and GABA accumulation, suggesting that ACC plays a crucial regulatory role in rice seed germination. These findings were further substantiated by monitoring the enzymatic activity of glutamate decarboxylase (GAD) throughout the germination process. Notably, while higher ACCs negatively impacted rice seed growth, pH variations within the tested range showed no adverse effects on seed development. The results show that optimal SAEW parameters, considering both pH and ACC, should be carefully determined for practical applications in rice seed production.